Negative pole piece, preparation method of negative pole piece, battery monomer, battery and power utilization device

CN119487643APending Publication Date: 2025-02-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380048928.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-03-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

While the energy density of existing secondary batteries is increased, the expansion effect of the negative electrode plate is intensified, affecting ion dynamics, resulting in poor charge and discharge performance.

Method used

Adopting the design of the negative electrode plate, the film layer includes the first part of the first carbon-based active material with high powder compaction density and the second part of the second carbon-based active material composed of secondary particles. The micro-oxidation treatment improves the performance of graphite. The degree of graphitization and adhesion, controlling the powder compaction density and particle distribution, work together to improve the energy density and cycle performance of the battery.

Benefits of technology

It achieves high energy density and good charge and discharge performance, reduces the expansion of the negative electrode piece, and improves the cycle performance and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487643A_ABST
    Figure CN119487643A_ABST
Patent Text Reader

Abstract

The invention provides a negative pole piece and a preparation method thereof, a battery monomer, a battery and an electric device. The negative pole piece comprises a current collector and a film layer arranged on the current collector, the film layer comprises a first part and a second part which are arranged along the thickness direction of the film layer, the first part is arranged on the current collector, and the second part is arranged on the first part; the first portion comprises a first carbon-based active material, the second portion comprises a second carbon-based active material, the second carbon-based active material comprises secondary particles, and the powder compaction density of the first carbon-based active material is greater than the powder compaction density of the second carbon-based active material. When the negative pole piece is applied to the battery, the battery can have high energy density and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Negative electrode sheet and preparation method thereof, battery cell, battery and electrical device Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode plate and a preparation method thereof, a battery cell, a battery and an electrical device. Background Art

[0002] In recent years, the application scope of secondary batteries has become increasingly extensive. They are widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. As secondary batteries have achieved great development, higher requirements have been placed on their energy density, cycle performance, and other aspects.

[0003] Increasing the active material loading on the negative electrode sheet is one way to improve battery energy density. However, as the active material loading increases, the thickness of the negative electrode sheet increases. This exacerbates the expansion of the negative electrode active material layer during battery cycling, making it more prone to collapse and severely impacting ion dynamics. How to achieve both high energy density and good charge-discharge performance in secondary batteries remains a pressing technical challenge.

[0004] Summary of the Invention

[0005] The present application is made in view of the above-mentioned technical problems, and its purpose is to provide a negative electrode plate, a method for preparing a negative electrode plate, a battery cell, a battery and an electrical device. The negative electrode plate is used in a battery to enable the battery to have high energy density and good charge and discharge performance.

[0006] In a first aspect, the present application provides a negative electrode plate, comprising a negative electrode current collector and a film layer arranged on the negative electrode current collector; the film layer comprises a first part and a second part arranged along the thickness direction of the film layer, the first part is arranged on the current collector, and the second part is arranged on the first part; the first part comprises a first carbon-based active material, the second part comprises a second carbon-based active material, the second carbon-based active material comprises secondary particles, and the powder compaction density of the first carbon-based active material is greater than the powder compaction density of the second carbon-based active material.

[0007] In the embodiments of the present application, on the one hand, a first carbon-based active material is arranged in the first part, and the first carbon-based active material has a larger powder compaction density than the second carbon-based active material, which can provide a higher active material loading for the negative electrode plate, thereby providing a higher energy density for the battery; on the other hand, a second carbon-based active material is arranged in the second part, and the second carbon-based active material includes secondary particles, so that the second carbon-based active material has good ion dynamics. Therefore, the first carbon-based active material arranged in the first part and the second carbon-based active material arranged in the second part work synergistically, so that the battery has high energy density while also having good charge and discharge performance and cycle performance.

[0008] In some embodiments, the powder compaction density ρ2 of the second carbon-based active material under a pressure of 50,000 N satisfies: 1.70 g / cc≤ρ2≤1.90 g / cc; optionally, 1.80 g / cc≤ρ2≤1.90 g / cc.

[0009] In some embodiments, the second carbon-based active material satisfies at least one of the following (1)-(3): (1) The specific surface area SSA2 of the second carbon-based active material satisfies: 1.2 m 2 / g≤SSA2≤3.0m 2 / g; optionally, 1.5m 2 / g≤SSA2≤2.0m 2 / g; (2) volume particle size distribution D of the second carbon-based active material V 502 meets: 8.0μm≤D V 502≤20.0μm; optionally, 10.0μm≤D V 502≤18.0μm; (3) the mass specific capacity C of the second carbon-based active material m2 Meet: 340mAh / g≤C m2 ≤355mAh / g; optionally, 343mAh / g≤C m2 ≤350mAh / g.

[0010] In some embodiments, the OI value of the negative electrode plate satisfies: 10≤OI≤30.

[0011] In some embodiments, the powder compaction density ρ1 of the first carbon-based active material under a pressure of 50,000 N satisfies: 1.70 g / cc≤ρ1≤2.05 g / cc; optionally, 1.80 g / cc≤ρ1≤2.05 g / cc.

[0012] In an embodiment of the present application, when a first carbon-based active material is provided in the first part of the membrane layer and a second carbon-based active material is provided in the second part of the membrane layer, by controlling the powder compaction density of the first carbon-based active material within an appropriate range, the inner side of the membrane layer close to the current collector has a higher powder compaction density, thereby being able to provide a high energy density for the battery.

[0013] In some embodiments, the first carbon-based active material includes artificial graphite that has been subjected to a slight oxidation treatment.

[0014] In an embodiment of the present application, the first carbon-based active material includes artificial graphite that has been micro-oxidized. Compared with ordinary artificial graphite, the artificial graphite that has been micro-oxidized has a larger powder particle size, a higher degree of graphitization, greater adhesion between particles, and a high powder compaction density, which can provide a higher energy density for the battery.

[0015] In some embodiments, the powder compaction density of the artificial graphite after micro-oxidation treatment under a pressure of 50000N is 1-1 Satisfies: 1.80g / cc≤ρ 1-1 ≤2.05g / cc; optionally, 1.90g / cc≤ρ 1-1 ≤2.00g / cc.

[0016] The embodiments of the present application help to increase the powder compaction density of the first carbon-based active material by controlling the powder compaction density of the artificial graphite after micro-oxidation treatment within a suitable range, thereby increasing the powder compaction density on the inner side of the membrane layer and providing high energy density for the battery.

[0017] In some embodiments, the artificial graphite after micro-oxidation treatment satisfies at least one of the following (4)-(6): (4) The specific surface area SSA1 of the artificial graphite after micro-oxidation treatment satisfies: 1.6m 2 / g≤SSA1≤3.5m 2 / g; optionally, 1.8m 2 / g≤SSA1≤2.8m 2 / g; (5) the volume particle size distribution D of the artificial graphite after micro-oxidation treatment V 501 meets: 10.0μm≤D V 501≤30.0μm; optionally, 13.0μm≤D V 501≤25.0μm; (6) the mass specific capacity C of the artificial graphite after micro-oxidation treatment m1 Meet: 350mAh / g≤C m1 ≤365mAh / g; optionally, 355mAh / g≤C m1 ≤362mAh / g.

[0018] In some embodiments, the artificial graphite after micro-oxidation treatment includes secondary particles.

[0019] In the embodiments of the present application, at least a portion of the artificial graphite after micro-oxidation treatment is secondary particles, which helps improve the ion dynamics of the artificial graphite after micro-oxidation treatment, thereby also improving the ion dynamics of the first carbon-based active material disposed in the first portion. This further enhances the ion conductivity of the negative electrode plate, helping to improve the charge and discharge performance of the battery. In addition, the strong bonding between the secondary particles and the strong cohesion within the negative electrode plate help to reduce the expansion effect of the negative electrode plate during battery cycling, thereby helping to improve the battery's cycling performance and service life.

[0020] In some embodiments, in the artificial graphite after micro-oxidation treatment, the number of the secondary particles accounts for n and satisfies: 70%≤n≤90%.

[0021] In some embodiments, the first carbon-based active material further comprises natural graphite.

[0022] In the embodiments of the present application, the introduction of natural graphite into the first carbon-based active material helps to increase the gram capacity of the first carbon-based active material, and further helps to improve the energy density of the battery.

[0023] In some embodiments, the ratio of the mass m2 of the natural graphite to the mass m1 of the first carbon-based active material satisfies: 0%<m2 / m1≤50%.

[0024] In some embodiments, a ratio of the thickness h1 of the first portion to the thickness h of the film layer satisfies: 40%≤h1 / h≤60%.

[0025] In some embodiments, a ratio of a thickness h2 of the second portion to a thickness h of the film layer satisfies: 40%≤h2 / h≤60%.

[0026] In a second aspect, a method for preparing a negative electrode sheet is provided, comprising: providing a current collector; preparing a first portion of a film layer on the current collector; wherein the first portion includes a first carbon-based active material; preparing a second portion of the film layer on the first portion of the film layer, wherein the second portion includes a second carbon-based active material, the second carbon-based active material includes secondary particles, and the powder compaction density of the first carbon-based active material is greater than the powder compaction density of the second carbon-based active material.

[0027] In an embodiment of the present application, the membrane layer is prepared into a first part including a first carbon-based active material and a second part including a second carbon-based active material. The first carbon-based active material has a large compaction density and can provide a higher energy density for the battery; the secondary particles in the second carbon-based active material can provide good ion dynamics. Therefore, the negative electrode plate prepared by the above method has a synergistic effect in structure and material, and while realizing a high energy density battery, it also enables the battery to have good charge and discharge performance and cycle performance.

[0028] In a third aspect, a battery cell is provided, comprising the negative electrode sheet of any embodiment of the first aspect of the present application; or a negative electrode sheet prepared according to the method for preparing a negative electrode sheet of any embodiment of the second aspect of the present application.

[0029] In a fourth aspect, a battery is provided, comprising the battery cell of any embodiment of the third aspect of the present application.

[0030] In a fifth aspect, an electrical device is provided, which includes the battery cell in any embodiment of the third aspect of the present application, and / or the battery in any embodiment of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. Those skilled in the art can also derive other drawings based on the drawings without inventive effort. In the drawings, the drawings are not drawn to scale.

[0032] FIG1 is a schematic structural diagram of a negative electrode plate of the present application.

[0033] FIG2 is a schematic flow chart of a method for preparing a negative electrode sheet according to the present application.

[0034] FIG3 is a schematic diagram of a battery cell of the present application.

[0035] FIG4 is a schematic diagram of a battery module of the present application.

[0036] FIG5 is a schematic diagram of a battery according to the present application.

[0037] FIG6 is another schematic diagram of a battery according to the present application. DETAILED DESCRIPTION

[0038] Below, with appropriate reference to the accompanying drawings, the embodiments of the negative electrode sheet, the method for preparing the negative electrode sheet, the battery cell, the battery, and the electrical device of the present application are described in detail. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0039] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0040] In the description of this application, it should be noted that, unless otherwise specified, "multiple" means more than two; the terms "upper", "lower", "left", "right", "inside", "outside", etc., indicating directions or positional relationships, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on this application. In addition, the terms "first", "second", "third", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance. "Vertical" is not strictly perpendicular, but is within the allowable error range. "Parallel" is not strictly parallel, but is within the allowable error range.

[0041] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0042] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0043] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0045] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0046] Unless otherwise specified, the following terms have the following meanings. Any undefined terms have their generally accepted meanings in the art.

[0047] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery's charge and discharge process, active ions are embedded in and released from the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator is positioned between the positive and negative electrodes, primarily to prevent a short circuit between the positive and negative electrodes while allowing ions to pass through. In some embodiments, the battery described herein is also referred to as a secondary battery.

[0048] This application uses lithium-ion batteries as an example. Lithium-ion batteries are a typical type of secondary battery. Because they rely on the chemical reaction of lithium ions intercalating and disintercalating between the positive and negative electrodes to charge and discharge, lithium-ion batteries are also called rocking-chair batteries. During charging, lithium ions are released from the positive electrode, moved to the negative electrode, and then intercalated. During discharge, lithium ions are released from the negative electrode, moved to the positive electrode, and then intercalated.

[0049] It should be understood that the "lithium insertion" and "intercalation" processes described in this application refer to the process in which lithium ions are embedded in the positive electrode material and the negative electrode material due to electrochemical reactions, and the "de-lithiumization", "de-lithiumization" and "de-intercalation" processes described in this application refer to the process in which lithium ions are removed from the positive electrode material and the negative electrode material due to electrochemical reactions.

[0050] First, some technical terms involved in the embodiments of this application are introduced.

[0051] "Carbon-based active materials" refer to materials with carbon as the matrix, including carbon-based composites, fiber-reinforced composites, graphite and graphene materials, etc.

[0052] "Micro-oxidation treatment" refers to the process of placing the material in an oxidizing atmosphere at a temperature of 600°C-900°C to carry out a micro-oxidation reaction.

[0053] "Primary particles" refer to carbon-based particles obtained by direct crushing, shaping, graphitization, etc. of raw materials, also known as carbon-based single particles.

[0054] "Secondary particles" refer to particles with a carbon matrix, which are formed from primary particles through agglomeration, granulation or other means, and then obtained through steps such as graphitization.

[0055] With the increasing application of batteries, higher requirements are placed on the energy density of batteries. Increasing the powder compaction density of the positive and negative electrode sheets allows the positive and negative electrode sheets to carry more positive and negative active materials per unit area or volume, which can effectively improve the energy density of the battery. Taking the negative electrode sheet as an example, the thicker the film layer of the negative electrode sheet and the greater the compaction density, the higher the energy density that the negative electrode sheet can contribute. However, the current collector can only withstand a limited amount of compression, and a thicker film layer will cause the expansion effect of the negative electrode sheet to intensify during the battery cycle. The film layer is more likely to collapse, which is not conducive to the release and embedding of active ions in the negative electrode active material, thereby seriously affecting the ion dynamics of the battery and resulting in poor rate performance.

[0056] In view of this, an embodiment of the present application provides a negative electrode plate, the film layer of the negative electrode plate includes a first part arranged on the negative electrode collector and a second part arranged on the first part, the first part includes a first carbon-based active material, the second part includes a second carbon-based active material, and the first carbon-based active material has a large compaction density, and the second carbon-based active material includes secondary particles. The synergistic effect of the first carbon-based active material and the second carbon-based active material enables the negative electrode plate to provide high energy density for the battery while also helping to improve the battery's charge and discharge performance and cycle performance.

[0057] Next, the negative electrode sheet, positive electrode sheet, separator and other parts of the battery are introduced in detail.

[0058] [Negative electrode]

[0059] The negative electrode sheet generally includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material. It should be understood that the negative electrode film layer is a film layer disposed on the negative electrode current collector.

[0060] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0061] Alternatively, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base layer (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0062] Alternatively, the negative electrode active material may be a negative electrode active material for batteries that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0063] Optionally, the negative electrode film layer further includes a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0064] Optionally, in one embodiment, the negative electrode film layer further includes a conductive agent, which can be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0065] Optionally, the negative electrode film layer further includes other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)).

[0066] FIG1 is a schematic structural diagram of a negative electrode plate provided in an embodiment of the present application.

[0067] As shown in FIG1 , the negative electrode plate 1 includes a negative electrode current collector 11 and a film layer 12 disposed on the negative electrode current collector 11 .

[0068] The film layer 12 includes a first portion 12a and a second portion 12b. The first portion 12a is disposed on the negative electrode current collector 11, and the second portion 12b is disposed on the first portion 12a.

[0069] The first portion 12a includes a first carbon-based active material, the second portion 12b includes a second carbon-based active material, the second carbon-based active material includes secondary particles, and the powder compaction density of the first carbon-based active material is greater than the powder compaction density of the second carbon-based active material.

[0070] Specifically, the film layer 12 is the above-mentioned negative electrode film layer. In the negative electrode plate 1, the first part 12a of the film layer 12 is provided with a first carbon-based active material, and the second part 12b of the film layer 12 is provided with a second carbon-based active material. The powder compaction density of the first carbon-based active material is greater than that of the second carbon-based active material. Therefore, the inner film layer 12 of the negative electrode plate 1 away from the electrolyte has a higher compaction density, which can provide a higher energy density for the battery. The secondary particles in the second carbon-based active material can provide a large number of active sites for the electrochemical reaction of the battery, which helps to improve the ion dynamics of the outer film layer 12 of the negative electrode plate 1 close to the electrolyte, thereby providing the battery with good charge and discharge capacity and cycle performance.

[0071] Optionally, the powder compaction density ρ2 of the second carbon-based active material under a pressure of 50,000 N satisfies: 1.70 g / cc≤ρ2≤1.90 g / cc; optionally, 1.80 g / cc≤ρ2≤1.90 g / cc.

[0072] Specifically, ρ2 can be 1.70 g / cc, 1.72 g / cc, 1.74 g / cc, 1.76 g / cc, 1.80 g / cc, 1.82 g / cc, 1.84 g / cc, 1.86 g / cc, 1.88 g / cc, 1.90 g / cc, or a value within the range obtained by combining any two of the above values.

[0073] Optionally, the second carbon-based active material satisfies at least one of the following (1)-(3):

[0074] (1) The specific surface area SSA2 of the second carbon-based active material satisfies: 1.2 m 2 / g≤SSA2≤3.0m 2 / g; optionally, 1.5m 2 / g≤SSA2≤2.0m 2 / g.

[0075] (2) Volume particle size distribution D of the second carbon-based active material V 502 meets: 8.0μm≤D V 502≤20.0μm; optionally, 10.0μm≤D V 502≤18.0μm.

[0076] (3) Mass specific capacity C of the second carbon-based active material m2 Meet: 350mAh / g≤C m2 ≤365mAh / g; optionally, 355mAh / g≤C m2 ≤362mAh / g.

[0077] Specifically, SSA2 can be 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g, 2.2m 2 / g, 2.4m 2 / g, 2.6m 2 / g, 2.8m 2 / g, 3.0m 2 / g, or its value is within the range obtained by combining any two of the above values.

[0078] D V502 can be 8 μm, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, or a value within the range obtained by combining any two of the above values.

[0079] C m2 It can be 350mAh / g, 352mAh / g, 354mAh / g, 356mAh / g, 358mAh / g, 360mAh / g, 362mAh / g, 365mAh / g, or its numerical range is within the range obtained by combining any two of the above numerical values.

[0080] Generally speaking, the higher the orientation index (OI value) of the negative electrode sheet 1 , the lower its ion dynamics.

[0081] Optionally, the OI value of the negative electrode plate 1 satisfies: 10≤OI≤30.

[0082] Specifically, the OI value can be 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, or a numerical range thereof within the range obtained by combining any two of the above numerical values.

[0083] In this embodiment, by controlling the OI value of the negative electrode plate 1 within a suitable range, the ion dynamics of the first carbon-based active material is improved, thereby helping to improve the charge and discharge performance and cycle performance of the battery.

[0084] Optionally, the powder compaction density ρ1 of the first carbon-based active material under a pressure of 50,000 N satisfies: 1.70 g / cc≤ρ1≤2.05 g / cc; optionally, 1.80 g / cc≤ρ1≤2.05 g / cc.

[0085] Specifically, ρ1 can be 1.70g / cc, 1.72g / cc, 1.74g / cc, 1.76g / cc, 1.80g / cc, 1.82g / cc, 1.84g / cc, 1.86g / cc, 1.88g / cc, 1.90g / cc, 1.92g / cc, 1.94g / cc, 1.96g / cc, 1.98g / cc, 2.00g / cc, 2.02g / cc, 2.04g / cc, 2.05g / cc, or its value is within the range obtained by combining any two of the above values.

[0086] In this embodiment, by controlling the powder compaction density ρ1 of the first carbon-based active material within an appropriate range, on the one hand, the first part 12a of the membrane layer 12 has a higher powder compaction density, thereby increasing the contribution of the first part 12a to the active material loading of the negative electrode plate 1; on the other hand, the powder compaction density of the first part 12a is controlled not to exceed the threshold value, thereby reducing the possibility of damaging the negative electrode current collector.

[0087] In some embodiments, the first carbon-based active material includes artificial graphite that has been subjected to a slight oxidation treatment.

[0088] Specifically, compared to conventional artificial graphite, artificial graphite that has undergone a micro-oxidation treatment has the advantages of larger particle size, higher degree of graphitization, higher specific capacity, and higher powder compaction density. As the first carbon-based active material, or as a portion of the first carbon-based active material, it can contribute high energy density to the negative electrode plate 1. Furthermore, the micro-oxidation treated artificial graphite particles exhibit greater adhesion, resulting in stronger cohesion in the inner film layer 12 of the negative electrode plate 1 and less expansion during battery cycling, thereby improving the battery's cycling performance and service life.

[0089] Optionally, the powder compaction density of the artificial graphite after micro-oxidation treatment under a pressure of 50000N is 1-1 Satisfies: 1.80g / cc≤ρ 1-1 ≤2.05g / cc; optionally, 1.90g / cc≤ρ 1-1 ≤2.00g / cc.

[0090] Specifically, ρ 1-1 It can be 1.80 g / cc, 1.85 g / cc, 1.90 g / cc, 1.95 g / cc, 2.00 g / cc, 2.05 g / cc, or a value within the range obtained by combining any two of the above values.

[0091] In this embodiment, the powder compaction density ρ of the artificial graphite after micro-oxidation treatment is controlled. 1-1 Within a suitable range, it helps to increase the powder compaction density ρ1 of the first carbon-based active material, thereby helping to increase the powder compaction density of the first portion 12a of the membrane layer 12, providing a high energy density for the battery while reducing the possibility of damaging the negative electrode current collector.

[0092] Optionally, the artificial graphite after micro-oxidation treatment satisfies at least one of the following (4)-(6):

[0093] (4) The specific surface area SSA1 of the artificial graphite after micro-oxidation treatment meets the following requirements: 1.6 m 2 / g≤SSA1≤3.5m 2 / g; optionally, 1.8m 2 / g≤SSA1≤2.8m 2 / g.

[0094] (5) Volume particle size distribution D of artificial graphite after micro-oxidation treatment V 501 meets: 10.0μm≤D V501≤30.0μm; optionally, 13.0μm≤D V 501≤25.0μm.

[0095] (6) Mass specific capacity C of artificial graphite after micro-oxidation treatment m1 Meet: 350mAh / g≤C m1 ≤365mAh / g; optionally, 355mAh / g≤C m1 ≤362mAh / g.

[0096] Specifically, SSA1 can be 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g, 2.1m 2 / g, 2.2m 2 / g, 2.3m 2 / g, 2.4m 2 / g, 2.5m 2 / g, 2.6m 2 / g, 2.7m 2 / g, 2.8m 2 / g, 2.9m 2 / g, 3.0m 2 / g, 3.1m 2 / g, 3.2m 2 / g, 3.3m 2 / g, 3.4m 2 / g, 3.5m 2 / g, or its value is within the range obtained by combining any two of the above values.

[0097] D V 501 can be 10μm, 12μm, 13μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 25μm, 26μm, 28μm, 30μm, or its value is within the range obtained by combining any two of the above values.

[0098] C m1 It can be 350mAh / g, 352mAh / g, 354mAh / g, 355mAh / g, 356mAh / g, 358mAh / g, 360mAh / g, 362mAh / g, 364mAh / g, 365mAh / g, or its numerical range is within the range obtained by combining any two of the above numerical values.

[0099] Optionally, the artificial graphite after the micro-oxidation treatment includes secondary particles.

[0100] Specifically, due to the formation and characteristics of the secondary particles themselves, in the electrochemical reaction, the secondary particles can expose more active sites, thereby helping to improve the ion dynamics of the battery.

[0101] In this embodiment, the artificial graphite after micro-oxidation treatment is composed of at least part of secondary particles, which can increase the active sites of the artificial graphite after micro-oxidation treatment in the electrochemical reaction, and help increase the active sites of the first carbon-based active material. As a result, the inner film layer 12 of the negative electrode plate 1 away from the electrolyte also has good ion dynamics, which helps to further improve the charge and discharge performance and cycle performance of the battery.

[0102] It should be understood that secondary particles are a morphological property of the material. The artificial graphite after micro-oxidation treatment includes secondary particles. The artificial graphite after micro-oxidation treatment may be entirely secondary particles, or partially secondary particles.

[0103] In one example, the first carbon-based active material includes only artificial graphite after micro-oxidation treatment. The artificial graphite after micro-oxidation treatment may be all secondary particles, or only a portion of the artificial graphite after micro-oxidation treatment may be secondary particles, and the remaining artificial graphite after micro-oxidation treatment does not have the morphology of secondary particles.

[0104] In another example, the first carbon-based active material includes artificial graphite after micro-oxidation treatment and artificial graphite. The artificial graphite after micro-oxidation treatment may be secondary particles, and the artificial graphite does not have the morphology of secondary particles; the artificial graphite may be secondary particles, and the artificial graphite after micro-oxidation treatment does not have the morphology of secondary particles; the artificial graphite after micro-oxidation treatment and the artificial graphite may both be secondary particles; and part of the artificial graphite after micro-oxidation treatment and part of the artificial graphite are secondary particles, and the remaining artificial graphite after micro-oxidation treatment and the remaining artificial graphite do not have the morphology of secondary particles.

[0105] Optionally, in the artificial graphite after micro-oxidation treatment, the proportion n of secondary particles satisfies: 70%≤n≤90%.

[0106] Specifically, n may be 70%, 75%, 80%, 85%, 90%, or any value within the range obtained by combining any two of the above values.

[0107] Optionally, the first carbon-based active material further includes natural graphite.

[0108] Natural graphite has a higher specific capacity than artificial graphite. In this embodiment, the introduction of natural graphite into the first carbon-based active material helps increase the specific capacity of the first carbon-based active material. This further increases the energy density of the inner film layer 12 of the negative electrode plate 1, thereby further improving the energy density of the battery.

[0109] Optionally, the ratio of the mass m2 of the natural graphite to the mass m1 of the first carbon-based active material satisfies: 0%<m2 / m1≤50%.

[0110] Specifically, m2 / m1 can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or its value is within the range obtained by combining any two of the above values.

[0111] It should be understood that in the case where the first carbon-based active material does not include natural graphite, m2 / m1 may be 0.

[0112] Optionally, as shown in FIG1 , the ratio of the thickness h1 of the first portion 12 a to the thickness h of the film layer 12 satisfies: 40%≤h1 / h≤60%.

[0113] Specifically, h1 / h can be 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, or its value is within the range obtained by combining any two of the above values.

[0114] Optionally, as shown in FIG1 , the ratio of the thickness h2 of the second portion 12 b to the thickness h of the film layer 12 satisfies: 40%≤h2 / h≤60%.

[0115] Specifically, h2 / h can be 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, or its value is within the range obtained by combining any two of the above values.

[0116] In this embodiment, by controlling the proportion of the thickness of the first part 12a and the second part 12b of the film layer 12 in the film layer 12, the energy density of the negative electrode plate 1 can be flexibly adjusted according to the needs of different batteries to adapt to more different types of batteries.

[0117] In some embodiments, the negative electrode sheet 1 can be prepared in the following manner: the components for preparing the negative electrode sheet are separately formed into negative electrode slurries. For example, the first carbon-based active material, the conductive agent, the binder, and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a first slurry. The second carbon-based active material, the conductive agent, the binder, and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a second slurry. The first slurry and the second slurry are then coated on the negative electrode current collector. After drying, cold pressing, and other processes, the negative electrode sheet 1 can be obtained.

[0118] [Positive electrode]

[0119] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.

[0120] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0121] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0122] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0123] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.

[0124] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0125] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0126] [Electrolytes]

[0127] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0128] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0129] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0130] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0131] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0132] [Isolation film]

[0133] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0134] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0135] Next, the method for preparing the negative electrode sheet according to the embodiment of the present application is introduced in detail.

[0136] FIG2 is a schematic flow chart of a method for preparing a negative electrode sheet according to an embodiment of the present application. As shown in FIG2 , method 200 includes:

[0137] S201, providing a current collector 11.

[0138] S202 , preparing a first portion 12 a of the film layer 12 on the current collector.

[0139] S203 , preparing the second portion 12 b of the film layer 12 on the first portion 12 a .

[0140] The first portion 12a includes a first carbon-based active material, the second portion 12b includes a second carbon-based active material, the second carbon-based active material includes secondary particles, and the powder compaction density of the first carbon-based active material is greater than the powder compaction density of the second carbon-based active material.

[0141] In this embodiment, the film layer 12 of the negative electrode plate 1 is prepared in the form of a first part 12a and a second part 12b, wherein the first part 12a includes a first carbon-based active material with a large powder compaction density, which can provide a larger energy density for the battery; the second part 12b includes secondary particles, which can provide good ion dynamics for the negative electrode plate 1, thereby helping to improve the battery's charge and discharge performance and cycle performance.

[0142] Optionally, in S202, preparing the first portion 12a of the film layer 12 on the current collector includes:

[0143] S2011, preparing a first carbon-based active material.

[0144] S2012, preparing a first carbon-based active material into a first slurry.

[0145] S2013 , coating the first slurry on the current collector 11 to form a first portion 12 a .

[0146] Optionally, in S2011, preparing the first carbon-based active material includes:

[0147] S2011-1, preparation of artificial graphite.

[0148] S2011-2, put artificial graphite into the furnace, at 600℃-900℃, air flow rate 1m 3 / h-9m 3 / h, and a furnace tube speed of 2r / min-6r / min to perform a micro-oxidation reaction to obtain artificial graphite after micro-oxidation treatment; the artificial graphite after micro-oxidation treatment includes secondary particles.

[0149] In this embodiment, the above method can be used to prepare artificial graphite containing secondary particles that has been micro-oxidized. While helping to improve the energy density of the battery, it also helps to improve the expansion effect of the negative electrode during the battery cycle, further helping to improve the cycle performance and service life of the battery.

[0150] Optionally, in S2011-1, preparing artificial graphite includes:

[0151] S2011-1a, crushing raw materials, raw materials include coke.

[0152] S2011-1b, classifying the crushed raw materials to obtain a particle product whose volume particle size is within a preset volume particle size distribution range.

[0153] S2011-1c, shaping and removing fine powder from the granular product to obtain a first intermediate product.

[0154] S2011-1d, heat-treating the first intermediate product to obtain a second intermediate product.

[0155] S2011-1e, graphitizing the second intermediate product at 2800° C.-3200° C. to obtain artificial graphite.

[0156] Optionally, the powder compaction density ρ1 of the first carbon-based active material satisfies: 1.70 g / cc≤ρ1≤2.05 g / cc; optionally, 1.80 g / cc≤ρ1≤2.05 g / cc.

[0157] Optionally, the powder compaction density ρ2 of the second carbon-based active material satisfies: 1.70 g / cc≤ρ2≤1.90 g / cc; optionally, 1.80 g / cc≤ρ2≤1.90 g / cc.

[0158] Optionally, the powder compaction density ρ1 of the artificial graphite after micro-oxidation treatment under a pressure of 50000N satisfies: 1.80g / cc≤ρ 1-1 ≤2.05g / cc; optionally, 1.90g / cc≤ρ 1-1 ≤2.00g / cc.

[0159] Optionally, the artificial graphite after micro-oxidation treatment satisfies at least one of the following (4)-(6):

[0160] (4) The specific surface area SSA1 of the artificial graphite after micro-oxidation treatment meets the following requirements: 1.6 m 2 / g≤SSA1≤3.5m 2 / g; optionally, 1.8m 2 / g≤SSA1≤2.8m 2 / g.

[0161] (5) Volume particle size distribution D of artificial graphite after micro-oxidation treatment V 501 meets: 10.0μm≤D V 501≤30.0μm; optionally, 13.0μm≤D V 501≤25.0μm.

[0162] (6) Mass specific capacity C of artificial graphite after micro-oxidation treatment m1 Meet: 350mAh / g≤C m1≤365mAh / g; optionally, 355mAh / g≤C m1 ≤362mAh / g.

[0163] Optionally, in the artificial graphite after micro-oxidation treatment, the proportion n of secondary particles satisfies: 70%≤n≤90%.

[0164] Optionally, in S2011, preparing the first carbon-based active material includes:

[0165] S2011-3, natural graphite is added to artificial graphite after slight oxidation treatment.

[0166] Optionally, the ratio of the mass m2 of the natural graphite to the mass m1 of the first carbon-based active material satisfies: 0%<m2 / m1≤50%.

[0167] Optionally, in S203, preparing the second portion 12b of the film layer 12 on the first portion 12a includes:

[0168] S2031, prepare a second carbon-based active material.

[0169] S2032, preparing a second carbon-based active material into a second slurry.

[0170] S2033 , coating a second slurry on the first portion 12 a of the film layer 12 to form a second portion 12 b .

[0171] Optionally, in S2031, preparing the second carbon-based active material includes:

[0172] S2031-1, crushing raw materials, raw materials include coke.

[0173] S2031-2, shaping and removing fine powder from the granular product to obtain a first intermediate product.

[0174] S2031-3, mixing the first intermediate product and asphalt, and pre-carbonizing the mixture at 300°C-600°C to obtain a third intermediate product.

[0175] S2031-4, graphitizing the third intermediate product at 3000° C. to obtain secondary particles.

[0176] In this embodiment, the above method can prepare a second carbon-based active material including secondary particles, so that the outer film layer 12 of the negative electrode plate 1 in contact with the electrolyte has good ion dynamics, which helps improve the charge and discharge performance and cycle performance of the battery.

[0177] Optionally, the second carbon-based active material satisfies at least one of the following (1)-(3):

[0178] (1) The specific surface area SSA2 of the second carbon-based active material satisfies: 1.2 m 2 / g≤SSA2≤3.0m 2 / g; optionally, 1.5m 2 / g≤SSA2≤2.0m 2 / g.

[0179] (2) Volume particle size distribution D of the second carbon-based active material V 502 meets: 8.0μm≤D V 502≤20.0μm; optionally, 10.0μm≤D V 502≤18.0μm.

[0180] (3) Mass specific capacity C of the second carbon-based active material m2 Meet: 340mAh / g≤C m2 ≤355mAh / g; optionally, 343mAh / g≤C m2 ≤350mAh / g.

[0181] In some embodiments, the positive electrode sheet, the negative electrode sheet 1 and the separator can be made into an electrode assembly through a winding process or a lamination process.

[0182] In some embodiments, the battery cell may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0183] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the battery cell may be a soft shell, such as a pouch-type soft shell. The soft shell may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0184] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square, or any other shape. For example, FIG3 shows a battery cell 300 having a square structure as an example.

[0185] Figure 4 shows an example battery module 400. Referring to Figure 4 , in the battery module 400, multiple battery cells 300 may be arranged sequentially along the length of the battery module 400. Of course, they may also be arranged in any other manner. Furthermore, the multiple battery cells 300 may be secured together using fasteners.

[0186] Optionally, in one embodiment, the battery module 400 may further include a housing having an accommodation space, and the plurality of battery cells 300 may be accommodated in the accommodation space.

[0187] Optionally, in one embodiment, the battery modules 400 may be assembled into a battery. The battery may contain one or more battery modules 400. The specific number may be selected by those skilled in the art according to the application and capacity of the battery.

[0188] Figures 5 and 6 illustrate an example battery 500. Referring to Figures 5 and 6, the battery 500 may include a battery box and multiple battery modules 400 disposed within the box. The battery box includes an upper case 501 and a lower case 502. The upper case 501 can be placed over the lower case 502 to form an enclosed space for accommodating the battery modules 400. The multiple battery modules 400 can be arranged in any manner within the battery box.

[0189] It should be understood that in other embodiments, the battery 500 is also referred to as a battery pack. The battery cells 300 may first be assembled into the battery module 400, and the battery 500 may be assembled from the battery module 400. Alternatively, the battery 500 may be assembled directly from the battery cells 300, omitting the intermediate battery module 400.

[0190] In addition, the present application also provides an electrical device, which includes at least one of the battery cell 300, battery module 400, or battery 500 provided in the present application. The battery cell 300, battery module 400, or battery 500 can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0191] As an electric device, a battery cell 300 , a battery module 400 , or a battery 500 may be selected according to its usage requirements.

[0192] As an example of an electric device, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the electric device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module can be used.

[0193] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0194] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0195] [Examples 1-26 and Comparative Examples 1-3]

[0196] Example 1

[0197] (1) Preparation of positive electrode sheet

[0198] The positive electrode active material, lithium iron phosphate, the conductive agent, acetylene black, and the binder, polyvinylidene fluoride (PVDF), are dissolved in the solvent N-methylpyrrolidone (NMP) and thoroughly stirred to form a positive electrode slurry. The slurry is then evenly coated onto the positive electrode current collector aluminum foil, dried, cold pressed, and slit to form the positive electrode sheets. The ratio of the mass of the positive electrode active material to the sum of the mass of the positive electrode active material, conductive agent, and binder is 95%-98%; alternatively, the ratio is 96%-97%.

[0199] (2) Preparation of negative electrode sheet

[0200] The first carbon-based active material, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are dissolved in the solvent deionized water and mixed evenly to obtain a first slurry. The second carbon-based active material, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are dissolved in the solvent deionized water and mixed evenly to obtain a second slurry. The first slurry is then evenly coated on the negative electrode current collector copper foil and dried to form the first part 12a of the film layer 12. The second slurry is then evenly coated on the first part 12a and dried to form the second part 12b of the film layer 12. The negative electrode sheet 1 is then obtained by cold pressing and slitting. Among them, the first carbon-based active material is artificial graphite that has been subjected to micro-oxidation treatment; the second carbon-based active material is carbon-based secondary particles.

[0201] In Example 1, the artificial graphite after micro-oxidation treatment is the first carbon-based active material. Its powder compaction density ρ 1-1 is 1.95 g / cc, and the powder compaction density ρ1 of the first carbon-based active material is ρ 1-1 The volume particle size distribution of artificial graphite after micro-oxidation treatment is equal to 1.95g / cc. V 501 is 18μm, and the mass specific capacity C of artificial graphite after micro-oxidation treatment m1The second carbon-based active materials are all secondary particles, and the powder compaction density ρ2 of the second carbon-based active materials is 1.82 g / cc. At this time, the powder compaction density ρ 2-1 The compacted density ρ2 of the second carbon-based active material is equal to 1.82 g / cc, and the volume particle size distribution D V 502 is 14μm, mass specific capacity C m2 The OI value of the negative electrode is 21.

[0202] It should be understood that the above-mentioned powder compaction density is the powder compaction density under a pressure of 50,000 N. The above-mentioned secondary particles are secondary particles without a coating layer. The materials with the above-mentioned volume particle size distribution can be tested by gas adsorption method to obtain the corresponding specific surface area, which will not be repeated here.

[0203] (3) Assembly of battery cells

[0204] The positive electrode sheet, the separator, and the negative electrode sheet 1 are stacked in order so that the separator is located between the positive electrode sheet and the negative electrode sheet 1 and can isolate the positive electrode sheet from the negative electrode sheet; the stacked components are then wound to obtain an electrode assembly; the electrode assembly is placed in a shell, dried, and then injected with a LiPF6 electrolyte with a mass fraction of 11%; after processes such as formation and standing, a battery cell 300 is obtained.

[0205] Example 2

[0206] Compared with Example 1, the first carbon-based active material of the negative electrode plate in Example 2 further includes natural graphite, wherein the mass ratio of natural graphite to the first carbon-based active material m2 / m1 is 50%, the powder compaction density ρ1 of the first carbon-based active material is 1.98 g / cc, and the powder compaction density ρ1 of the artificial graphite after micro-oxidation treatment is 1.98 g / cc. 1-1 The OI value of the negative electrode is 22.

[0207] Example 3

[0208] Compared with Example 1, Example 3 only changes the powder compaction density of the first carbon-based active material in the negative electrode sheet, that is, ρ1 is 1.8 g / cc in Example 3. The OI value of the negative electrode sheet is 19.

[0209] Example 4

[0210] Compared with Example 1, only the powder compaction density ρ1 of the first carbon-based active material in the negative electrode sheet was changed, that is, ρ1 was 2.05 g / cc in Example 4. The OI value of the negative electrode sheet was 24.

[0211] Example 5

[0212] Compared with Example 1, Example 5 only changes the volume particle size distribution of the artificial graphite after micro-oxidation treatment in the negative electrode plate, that is, D in Example 5 V 501 is 13μm. The OI value of the negative electrode is 19.

[0213] Example 6

[0214] Compared with Example 1, Example 6 only changes the volume particle size distribution of the artificial graphite after micro-oxidation treatment in the negative electrode plate, that is, D in Example 6 V 501 is 25μm. The OI value of the negative electrode is 22.

[0215] Example 7

[0216] Compared with Example 1, the volume particle size distribution D of the artificial graphite after micro-oxidation treatment in the negative electrode sheet of Example 7 is V 501 is 8μm.

[0217] Example 8

[0218] Compared with Example 1, the volume particle size distribution D of the artificial graphite after micro-oxidation treatment in the negative electrode sheet of Example 8 is V 501 is 27μm.

[0219] Example 9

[0220] Compared with Example 1, Example 7 only changes the gram capacity of the artificial graphite after slight oxidation treatment in the negative electrode plate, that is, Cm1 is 355 mAh / g. The OI value of the negative electrode plate is 23.

[0221] Example 10

[0222] Compared with Example 1, Example 8 only changes the gram capacity of the artificial graphite after slight oxidation treatment in the negative electrode plate, that is, Cm1 is 362 mAh / g. The OI value of the negative electrode plate is 22.

[0223] Example 11

[0224] Compared with Example 1, the gram capacity Cm1 of the artificial graphite after micro-oxidation treatment in the negative electrode sheet of Example 11 is 345 mAh / g.

[0225] Example 12

[0226] Compared with Example 1, the gram capacity Cm1 of the artificial graphite after micro-oxidation treatment in the negative electrode sheet of Example 12 is 365 mAh / g.

[0227] Example 13

[0228] Compared with Example 1, Example 13 only changed the number ratio of secondary particles in the artificial graphite after micro-oxidation treatment, that is, n was 70%. The OI value of the negative electrode plate was 19.

[0229] Example 14

[0230] Compared with Example 1, Example 14 only changed the number ratio of secondary particles in the artificial graphite after micro-oxidation treatment, that is, n was 90%. The OI value of the negative electrode plate was 22.

[0231] Example 15

[0232] Compared with Example 1, in the negative electrode sheet of Example 15, the number of secondary particles in the artificial graphite after micro-oxidation treatment accounts for 96%.

[0233] Example 16

[0234] Compared with Example 1, the second carbon-based active material in Example 16 further includes secondary particles having a coating layer, wherein the powder compaction density ρ2 of the second carbon-based active material is 1.80 g / cc, wherein the powder compaction density ρ2 of the secondary particles without the coating layer is 1.80 g / cc. 2-1 The OI value of the negative electrode is 15.

[0235] Example 17

[0236] Compared with Example 1, Example 17 only changed the powder compaction density of the second carbon-based active material in the negative electrode sheet, that is, ρ2 was 1.70 g / cc. The OI value of the negative electrode sheet was 20.

[0237] Example 18

[0238] Compared with Example 1, Example 18 only changed the powder compaction density of the second carbon-based active material in the negative electrode sheet, that is, ρ2 was 1.90 g / cc. The OI value of the negative electrode sheet was 23.

[0239] Example 19

[0240] Compared with Example 1, the powder compaction density ρ2 of the second carbon-based active material in the negative electrode sheet of Example 19 is 1.65 g / cc.

[0241] Example 20

[0242] Compared with Example 1, Example 20 only changes the volume particle size distribution of the second carbon-based active material in the negative electrode sheet, that is, D V 502 is 10μm. The OI value of the negative electrode is 21.

[0243] Example 21

[0244] Compared with Example 1, Example 21 only changes the volume particle size distribution of the second carbon-based active material in the negative electrode sheet, that is, D V 502 is 18μm. The OI value of the negative electrode is 20.

[0245] Example 22

[0246] Compared with Example 1, the volume particle size distribution D of the second carbon-based active material in the negative electrode sheet of Example 22 is V 502 is 6μm. The OI value of the negative electrode is 18.

[0247] Example 23

[0248] Compared with Example 1, Example 23 only changes the gram capacity of the second carbon-based active material in the negative electrode plate, that is, Cm1 is 343 mAh / g. The OI value of the negative electrode plate is 22.

[0249] Example 24

[0250] Compared with Example 1, Example 24 only changed the gram capacity of the second carbon-based active material in the negative electrode plate, that is, Cm1 was 350 mAh / g. The OI value of the negative electrode plate was 21.

[0251] Example 25

[0252] Compared with Example 1, the gram capacity Cm2 of the second carbon-based active material in the negative electrode sheet of Example 25 is 335 mAh / g.

[0253] Example 26

[0254] Compared with Example 1, the gram capacity Cm2 of the second carbon-based active material in the negative electrode sheet of Example 26 is 360 mAh / g.

[0255] Comparative Example 1

[0256] Compared with Example 1, the second carbon-based active material in Comparative Example 1 is a primary particle without a coating layer. The OI value of the negative electrode sheet is 32.

[0257] Comparative Example 2

[0258] Compared with Example 1, the powder compaction density ρ1 of the first carbon-based active material in the negative electrode sheet of Comparative Example 2 is 1.6 g / cc.

[0259] Comparative Example 3

[0260] Compared with Example 1, the powder compaction density ρ2 of the second carbon-based active material in the negative electrode sheet of Comparative Example 3 is 2.00 g / cc.

[0261] Please refer to Table 1 for specific parameter settings of the embodiment and comparative example.

[0262] In Table 1, ρ1 represents the powder compaction density of the first carbon-based active material under a pressure of 50,000 N, ρ 1-1 represents the powder compaction density of artificial graphite after micro-oxidation treatment under a pressure of 50000N, D V 501 represents the volume particle size distribution of the artificial graphite after micro-oxidation treatment, Cm1 represents the gram capacity of the artificial graphite after micro-oxidation treatment, n represents the number ratio of secondary particles in the artificial graphite after micro-oxidation treatment, m2 / m1 represents the ratio of the mass of natural graphite in the first carbon-based active material to the mass of the first carbon-based active material, ρ2 represents the powder compaction density of the second carbon-based active material under a pressure of 50000N, ρ 2-1 represents the powder compaction density of the secondary particles without coating layer under 50000N pressure, D V 502 represents the volume particle size distribution of the second carbon-based active material, Cm1 represents the gram capacity of the second carbon-based active material, OI represents the OI value of the negative electrode sheet 1, that is, the orientation index, "micro-oxidized AG" represents micro-oxidized artificial graphite, "NG" represents natural graphite, "secondary particles" represent carbon-based secondary particles without a coating layer, "primary particles" represent carbon-based primary particles without a coating layer, and "secondary particles (coated)" represent carbon-based secondary particles with a coating layer.

[0263] The battery performance test results of the above Examples 1-26 and Comparative Examples 1-3 are detailed in Table 2 and Table 3.

[0264] Table 2 Test results of battery charging time in different embodiments and comparative examples

[0265] Table 3 Cycle number and full charge expansion test results of different embodiments

[0266] A performance comparison between Example 1 and Comparative Examples 2 and 3 shows that the charging time of the lithium-ion battery of Example 1 is much shorter than that of the lithium-ion batteries of Comparative Examples 2 and 3. In Example 1, the powder compaction density of the first carbon-based active material is greater than the powder compaction density of the second carbon-based active material, while in Comparative Examples 2 and 3, the powder compaction density of the first carbon-based active material is less than the powder compaction density of the second carbon-based active material. This indicates that by controlling the powder compaction density of the first carbon-based active material to be greater than the powder compaction density of the second carbon-based active material, the lithium ion kinetics of the negative electrode sheet can be effectively improved, thereby improving the charge and discharge performance of the lithium-ion battery.

[0267] A performance comparison between the various examples and Comparative Example 1 shows that the charging time of the lithium-ion batteries in Examples 1-26 is shorter than that in Comparative Example 1. The OI values ​​of the negative electrode sheets 1 in Examples 1-26 are within the range of 10-30, while the OI value of Comparative Example 1 is 32, exceeding this range. This demonstrates that controlling the OI value of the negative electrode sheet 1 within this range can help improve the charge and discharge performance of the lithium-ion battery.

[0268] Compared with Example 1, the first carbon-based active material of Example 2 includes natural graphite. It can be seen from the various performances of the lithium-ion batteries of Examples 1 and 2 that the addition of natural graphite does not have a significant impact on the charge and discharge performance, cycle performance, and expansion of the lithium-ion battery. Natural graphite generally has a higher gram capacity than artificial graphite. Therefore, by introducing some natural graphite into the first carbon-based active material, it can help increase the energy density of the lithium-ion battery without affecting the above-mentioned performances of the lithium-ion battery.

[0269] A performance comparison of Examples 3 and 4 with Comparative Example 2 shows that the charging time of the lithium-ion batteries of Examples 3 and 4 is also shorter than that of the lithium-ion battery of Comparative Example 2. The powder compaction density of the first carbon-based active material in Examples 3 and 4 is 1.80 g / cc and 2.05 g / cc, respectively, which is within the numerical range of 1.70 g / cc-2.05 g / cc. In contrast, the powder compaction density of the first carbon-based active material in Comparative Example 2 is 1.6 g / cc, which is outside this numerical range. This demonstrates that controlling the powder compaction density of the first carbon-based active material within this numerical range helps improve the dynamics of the lithium-ion battery and reduces charging time.

[0270] By comparing the performance of Examples 5, 6 and 8 with that of Example 7, it can be seen that, while the charging time is better than that of the comparative example, the number of cycles of Examples 5, 6 and 8 is more than that of Example 7, and the full charge expansion ratio is less than that of Example 7. The average volume particle size (D V 501) are 13 μm, 25 μm, and 27 μm, respectively, which are within the numerical range of 10 μm-30 μm, while the average volume particle size of Example 7 is 8 μm, which exceeds the above numerical range. Therefore, it is shown that by controlling the average volume particle size of the artificial graphite after micro-oxidation treatment within the above numerical range, it is helpful to improve the cycle performance of the lithium-ion battery and improve the problem of battery expansion, thereby helping to improve the safety performance of the battery.

[0271] Compared with Example 9 and Example 10, the gram capacity (C m1) are 345mAh / g and 365mAh / g respectively, which exceeds the numerical range of 350mAh / g-365mAh / g, although the four embodiments are not much different in terms of charge and discharge performance, cycle performance, and expansion. However, in actual applications, the gram capacity of the material in Example 11 is too low, which makes the energy density of the battery too low and cannot meet the actual application requirements well. The gram capacity of Example 12 is too high, and the raw material preparation is extremely difficult, which is not conducive to large-scale production and application. Therefore, by controlling the gram capacity of the artificial graphite after micro-oxidation treatment within the above range, the charge and discharge performance, cycle performance and expansion of the lithium-ion battery can be improved, which is also conducive to the actual mass production and application of lithium-ion batteries.

[0272] In Examples 13-15, the proportion of secondary particles (n) in the artificial graphite after micro-oxidation treatment was regulated. Among them, the proportion of secondary particles in Example 13 was 70%, the proportion of secondary particles in Example 14 was 90%, and the proportion of secondary particles (n) in the artificial graphite after micro-oxidation treatment in Example 15 was as high as 96%, exceeding the numerical range of 70%-90%. When the charging time of the three examples is similar, it can be seen from the comparison of the performance data of Example 13 and Example 14 that the higher the proportion of secondary particles, the more cycles the battery has and the smaller the expansion rate. This shows that secondary particles help improve the ion dynamics of the electrode material and help improve the cycle performance of the lithium-ion battery; in addition, the secondary particles have a strong bonding force, which helps to improve the cohesion inside the negative electrode sheet, thereby helping to improve the expansion of the battery. According to the comparison of Example 15 with Example 13 and Example 14, it can be seen that the number of cycles and expansion of Example 15 are better than those of Example 13, but the number of cycles is reduced and the full charge expansion rate is increased compared with Example 14, indicating that the performance of the lithium-ion battery will not increase indefinitely as the proportion of secondary particles in the artificial graphite after micro-oxidation treatment increases. In addition, an excessively high proportion of secondary particles increases the difficulty of material processing. In other words, artificial graphite after micro-oxidation treatment with a secondary particle proportion of more than 90% is not easy to prepare. Therefore, by controlling the proportion of secondary particles in the artificial graphite after micro-oxidation treatment within the above-mentioned numerical range, the lithium-ion battery can have good charge and discharge performance, cycle performance and help improve the expansion of the lithium-ion battery.

[0273] In Example 16, the second carbon-based active material includes secondary particles with a coating layer. It can be seen that, similar to Example 1, by controlling the powder compaction density of the first carbon-based active material to be greater than the powder compaction density of the second carbon-based active material, a lithium-ion battery with improved charge and discharge performance, cycle performance, and expansion can be obtained.

[0274] Examples 17-19 regulated the powder compaction density of the second carbon-based active material. The powder compaction density of the second carbon-based active material in Examples 17 and 19 was 1.70 g / cc and 1.90 g / cc, respectively, which was within the numerical range of 1.70 g / cc-1.90 g / cc. However, the powder compaction density of the second carbon-based active material in Example 19 was 1.65 g / cc, which exceeded the above numerical range. A performance comparison of Example 19 with Examples 17 and 18 shows that although the charge-discharge performance, cycle performance, and expansion of the lithium-ion battery in Example 19 were improved compared to the comparative example, the aforementioned performance of the lithium-ion battery in Example 19 was inferior to that of Examples 17 and 18. This shows that by controlling the powder compaction density of the second carbon-based active material within the above numerical range, the lithium-ion battery can have good charge-discharge performance, cycle performance, and reduced expansion.

[0275] The average volume particle size (D V 502) was regulated, and the average volume particle size of the second carbon-based active material in Example 20 and Example 21 was 10μm and 18μm, respectively, which fell within the numerical range of 8μm-20μm. The average volume particle size of the second carbon-based active material in Example 22 was 6μm, which exceeded the above numerical range. Compared with the control example, the charge and discharge performance, cycle performance and expansion of the lithium-ion batteries in Examples 20-22 were improved. Although Example 22 has the shortest full charge time among the above three embodiments, the average volume particle size of the second carbon-based active material in Example 22 is too small, the material is difficult to prepare, and the number of cycles of the battery in Example 22 is reduced. Therefore, by controlling the average volume particle size of the second carbon-based active material within the above numerical range, while improving the charge and discharge performance of the lithium-ion battery, it also helps to improve the cycle performance of the lithium-ion battery.

[0276] Examples 23-26 show the gram capacity (C) of the second carbon-based active material. m2) were regulated, and the gram capacities of Examples 23-24 were 343mAh / g and 350mAh / g, respectively, that is, within the numerical range of 340mAh / g-355mAh / g, while the gram capacities of Examples 25-26 were 335mAh / g and 360mAh / g, respectively, that is, beyond the above numerical range. Although the four embodiments are not much different in terms of charge and discharge performance, cycle performance, and expansion. However, in actual applications, the gram capacity of the material in Example 25 is too low, which makes the energy density of the battery too low and cannot meet the needs of actual applications well. The gram capacity of Example 26 is too high, the raw materials are expensive and difficult to obtain, and it is not conducive to large-scale production and application. Therefore, by controlling the gram capacity of the second carbon-based active material within the above range, the charge and discharge performance, cycle performance and expansion of the lithium-ion battery can be improved, and it is also helpful to the actual mass production and application of lithium-ion batteries.

[0277] Next, the testing methods of the physical parameters and performance parameters mentioned in the embodiments of this application are briefly introduced.

[0278] 1. Test method for powder compaction density

[0279] The compacted density of a material's powder can be tested using methods known in the art. For example, referring to GB / T 24533-2009, an electronic pressure testing machine (such as the UTM7305) can be used. A certain amount of powder is placed on a compaction mold and various pressures are set. The thickness of the powder at each pressure is measured on the machine, and the compacted density at each pressure can be calculated.

[0280] 2. Test method for average volume particle size distribution

[0281] The volume particle size distribution of a material can be measured using methods known in the art. For example, referring to GB / T19077-2016 / ISO 13320:2009, a laser diffractometer can be used. After instrument commissioning and background measurement, sample preparation, and light signal acquisition, the instrument is used to calculate the scattering matrix using an appropriate optical model. Finally, the scattered light distribution is converted into a particle size distribution.

[0282] 3. Test method for gram capacity

[0283] PVDF, conductive carbon black (SP), and active materials are mixed in a specific ratio to form a negative electrode slurry. This is then coated onto copper foil and evenly spread with a scraper. The slurry is then dried, cold-pressed, and punched into sheets. The slurry is then assembled with a lithium sheet and separator to form a button cell. A LAND tester is used to perform charge-discharge cycles from 0.005V to 2V to determine the specific gram capacity of the active material.

[0284] 4. Orientation index (OI value) test method

[0285] The OI value of the material on the negative electrode sheet can be measured using methods known in the art, for example, by measuring the XRD pattern of the sample and calculating the OI value using C004 / C110.

[0286] 5. Charging time test method

[0287] At 25°C, charge at 0.33C for t minutes to 80% SOC, let it stand for 30 minutes, then discharge at 1C, let it stand for 30 minutes, and cycle 20 times. After fully charging, disassemble the battery and observe whether lithium is deposited at the negative electrode. If there is no lithium deposition, it indicates that the battery's room temperature charging time from 0% to 80% SOC is t minutes.

[0288] 6. Cycling performance test method

[0289] Assemble the full battery and perform a cycle test using a LAND tester with a charge rate of 0.5c and a discharge rate of 1c. The battery is repeatedly charged and discharged, and the number of cycles required for the battery capacity to decay by 80% is calculated, that is, the number of cycles required for the battery's capacity to decay by 80% at room temperature.

[0290] 7. Test method for volume expansion rate

[0291] At room temperature, measure the thickness d1 of the electrode. After the electrodes are assembled into a battery, charge the battery to 4.2V at 0.5C, let it stand for 3 minutes, disassemble the battery, and measure the thickness d2 of the electrode at this time. The full charge expansion rate can be calculated as (d2-d1) / d1×100%.

[0292] 8. Test method for the proportion of secondary particles

[0293] The percentage of secondary particles (n) in micro-oxidized artificial graphite can be determined by scanning electron microscopy (SEM) of the material. Specifically, the number of particles with secondary particle morphology (n2) and the number of all particles (n1) in the SEM are counted separately, and the ratio of the two is calculated: in other words, n = n2 / n1. To improve the accuracy of this ratio, the above particle counts can be performed on multiple SEM images of the material, and the percentage of secondary particles can be calculated based on the average of these results.

[0294] As an example, a SEM image can be obtained by:

[0295] A certain mass of the material to be tested (≤2g) is weighed and adhered to the conductive adhesive. The conductive adhesive is placed on a sample stage and dried. The treated sample stage is sent to a field emission scanning electron microscope (for example, a Zeiss Sigma300 scanning electron microscope) to capture the morphology of the material.

[0296] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate comprises: A negative electrode current collector and a film layer disposed on the negative electrode current collector; The film layer comprises a first portion and a second portion arranged along a thickness direction of the film layer, the first portion being arranged on the current collector, and the second portion being arranged on the first portion; The first part includes a first carbon-based active material, the second part includes a second carbon-based active material, the second carbon-based active material includes secondary particles, and the powder compaction density of the first carbon-based active material is greater than the powder compaction density of the second carbon-based active material.

2. The negative electrode sheet according to claim 1, characterized in that: The powder compaction density ρ2 of the second carbon-based active material under a pressure of 50000N satisfies: 1.70g / cc≤ρ2≤1.90g / cc; optionally, 1.80g / cc≤ρ2≤1.90g / cc.

3. The negative electrode sheet according to claim 1 or 2, characterized in that: The second carbon-based active material satisfies at least one of the following (1)-(3): (1) The specific surface area SSA2 of the second carbon-based active material satisfies: 1.2 m 2 / g≤SSA2≤3.0m 2 / g; optionally, 1.5m 2 / g≤SSA2≤2.0m 2 / g; (2) Volume particle size distribution D of the second carbon-based active material V 502 meets: 8.0μm≤D V 502≤20.0μm; optionally, 10.0μm≤D V 502≤18.0μm; (3) The mass specific capacity C of the second carbon-based active material m2 Meet: 340mAh / g≤C m2 ≤355mAh / g; optionally, 343mAh / g≤C m2 ≤350mAh / g.

4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The OI value of the negative electrode plate satisfies: 10≤OI≤30.

5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The powder compaction density ρ1 of the first carbon-based active material under a pressure of 50000N satisfies: 1.70g / cc≤ρ1≤2.05g / cc; optionally, 1.80g / cc≤ρ1≤2.05g / cc.

6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The first carbon-based active material includes artificial graphite that has been subjected to a micro-oxidation treatment.

7. The negative electrode sheet according to claim 6, characterized in that: The powder compaction density of the artificial graphite after micro-oxidation treatment under a pressure of 50000N is 1-1 Satisfy: 1.80g / cc≤ρ 1-1 ≤2.05g / cc; optionally, 1.90g / cc≤ρ 1-1 ≤2.00g / cc.

8. The negative electrode sheet according to claim 6 or 7, characterized in that: The artificial graphite after micro-oxidation treatment satisfies at least one of the following (4)-(6): (4) The specific surface area SSA1 of the artificial graphite after micro-oxidation treatment satisfies: 1.6 m 2 / g≤SSA1≤3.5m 2 / g; optionally, 1.8m 2 / g≤SSA1≤2.8m 2 / g; (5) Volume particle size distribution D of the artificial graphite after micro-oxidation treatment V 501 meets: 10.0μm≤D V 501≤30.0μm; optionally, 13.0μm≤D V 501≤25.0μm; (6) The mass specific capacity C of the artificial graphite after micro-oxidation treatment m1 Meet: 350mAh / g≤C m1 ≤365mAh / g; optionally, 355mAh / g≤C m1 ≤362mAh / g.

9. The negative electrode sheet according to any one of claims 6 to 8, characterized in that: The artificial graphite after micro-oxidation treatment includes secondary particles.

10. The negative electrode sheet according to claim 9, characterized in that: In the artificial graphite after micro-oxidation treatment, the number ratio n of the secondary particles satisfies: 70%≤n≤90%.

11. The negative electrode sheet according to any one of claims 1 to 10, characterized in that: The first carbon-based active material also includes natural graphite.

12. The negative electrode sheet according to claim 11, characterized in that: The ratio of the mass m2 of the natural graphite to the mass m1 of the first carbon-based active material satisfies: 0%<m2 / m1≤50%.

13. The negative electrode sheet according to any one of claims 1 to 12, characterized in that: The ratio of the thickness h1 of the first portion to the thickness h of the film layer satisfies: 40%≤h1 / h≤60%.

14. The negative electrode sheet according to any one of claims 1 to 13, characterized in that: The ratio of the thickness h2 of the second portion to the thickness h of the film layer satisfies: 40%≤h2 / h≤60%.

15. A method for preparing a negative electrode sheet, characterized in that: The method comprises: providing a current collector; Preparing a first portion of a film layer on the current collector; wherein the first portion includes a first carbon-based active material; A second portion of the membrane layer is prepared on the first portion of the membrane layer, wherein the second portion includes a second carbon-based active material, the second carbon-based active material includes secondary particles, and the powder compaction density of the first carbon-based active material is greater than the powder compaction density of the second carbon-based active material.

16. A battery cell, characterized in that: The battery cell comprises a negative electrode sheet as claimed in any one of claims 1 to 14; or A negative electrode sheet prepared according to the method of claim 15.

17. A battery, characterized in that: The battery comprises the battery cell as claimed in claim 16.

18. An electrical device, characterized in that: The electrical device comprises the battery cell according to claim 16 and / or the battery according to claim 17.